1995
DOI: 10.1021/jf00056a039
|View full text |Cite
|
Sign up to set email alerts
|

Levels of the Cholesterol-Elevating Diterpenes Cafestol and Kahweol in Various Coffee Brews

Abstract: The coffee diterpenes cafestol and kahweol raise serum cholesterol in humans. Each 10 mg of cafestol consumed per day elevates cholesterol by 5 mg/dL (0.13 mmol/L). Diterpene levels in various coffee brews were examined. Scandinavian boiled coffee contained (mean f SD) 3.0 f 2.8 mg, French press coffee 3.5 f 1.2 mg, and TurkisWGreek coffee 3.9 f 3.2 mg of cafestol per cup. Consumption of five cups per day of any of these coffee types could thus elevate serum cholesterol by 8-10 mgl dL. Italian espresso coffee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
138
1
11

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(162 citation statements)
references
References 18 publications
9
138
1
11
Order By: Relevance
“…Soxhlet extraction can be used to extract these compounds from the beans [84]. Further treatment includes saponification which is also used in preparation of coffee extract samples, and then, the samples are silylated [84,85]. Chartier et al [86] proposed a simplified procedure with automatic transesterification of the esters of diterpenes in a flow reactor.…”
Section: Determination Of Diterpenesmentioning
confidence: 99%
“…Soxhlet extraction can be used to extract these compounds from the beans [84]. Further treatment includes saponification which is also used in preparation of coffee extract samples, and then, the samples are silylated [84,85]. Chartier et al [86] proposed a simplified procedure with automatic transesterification of the esters of diterpenes in a flow reactor.…”
Section: Determination Of Diterpenesmentioning
confidence: 99%
“…The beans of these commercially important species have been analyzed extensively. The unsaponifiable lipid fraction of these beans is rich in two diterpenes specific for coffee: cafestol and kahweol ( Figure 1) (Viani, 1988;Urgert et al, 1995). The total diterpene content ranges from 1.3% to 1.9% (w/w) in green beans of Coffea arabica (commonly known as Arabica) and from 0.2% to 1.5% in beans of Coffea canephora (commonly known as Robusta) (Viani, 1988;Ratnayake et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…[4] The composition of coffee brew and the level of diterpenes in coffee brews may be influenced by coffee species, roasting degree, [2] and subsequent brewing methods. [5,6,7] Although elevation of low density lipoprotein and triglycerides may be the consequences of incautious coffee consumption and consequently ingestion of high amounts of diterpenes [8] , they are responsible for degradation of toxic substances and may offer protective effects against aflatoxin B1. [9] Moreover, much research has been undertaken and indicated the anti-carcinogenic [10] , anti-angiogenic and anti-inflammatory properties [11] of these diterpenes.…”
Section: Introductionmentioning
confidence: 99%
“…[7,15,16,17] Since diterpenes are relatively polar, [18] their extraction is carried out by organic solvents such as diethyl ether or tert-butyl methyl ether. [16,18,19,20] Numerous analytical methodologies have been developed for the determination of diterpenes in coffee samples, mainly, gas chromatography (GC) [5] , high performance liquid chromatography (HPLC), [4] or spectrophotometric techniques. [15] Since, mild temperatures is a key parameter for the preservation of sensitive compounds in extracts, application of HPLC is preferred over GC, mainly due to degradation of diterpenes and production of decomposition compounds under high temperatures (200-305 ºC) [5] of the GC system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation